Stroking Parameters during Continuous and Intermittent Exercise in Regional-Level Competitive Swimmers - Oliveira, M. F. M.; Caputo, F.; Dekerle, J.; Denadai, B. S. [UNESP]; Greco, C. C. [UNESP] (Georg Thieme Verlag Kg, 2012)
This study aimed to determine whether maximal lactate steady state (MLSS) represents a boundary above which not only physiological but also technical changes occur. on different days, 13 male swimmers (23 +/- 9 years) performed the following tests: 1) a 400-m all-out swim, to determine maximal aerobic speed (S-400); 2) a series of 30-min sub-maximal swims, to determine continuous MLSS (MLSSc), and; 3) a series of 12 x 150s sub-maximal swims, to determine intermittent MLSS (MLSSi). Stroke rate (SR), distance per stroke cycle (DS) and stroke index (SI) were analyzed at and above (102.5%) MLSSc and MLSSi. MLSSi (1.17 +/- 0.09 m.s(-1)) was significantly higher than MLSSc (1.13 +/- 0.08 m.s(-1)) while blood lactate concentration (mmol.L-1) was similar between the 2 conditions (4.3 +/- 1.1 and 4.4 +/- 1.5, respectively). The increase in SR and decreases in DS and SI were significant during MLSSi, 102.5% MLSSc and 102.5% MLSSi. During MLSSc, DS also decreased significantly (-3.6%) but with no change in SR or SI. Thus, stroking technique of regional-level competitive swimmers changes over time when they swim at or above MLSS. This is the case during both continuous and intermittent swimming, despite steady state blood lactate concentrations.
Keywords: swim technique; endurance; training; lactataemia